A long way to a simple diagnosis – a case report of an overlooked juvenile polyp - Kozłowska-Jalowska, Anna; Stróżyk, Agata; Majak, Paweł; Horvath, Andrea (Pediatria Polska - Polish Journal of Paediatrics, 2025)
Lower gastrointestinal bleeding (also known as rectal bleeding) is a common symptom reported to a pediatrician. It can be caused by a variety of medical conditions across different age groups, including in the majority, benign and common, such as annal fissure, rectal polyps or gastrointestinal infection. We report the case of a 10-year-old boy with an isolated juvenile polyp. The multi-symptoms and inappropriate/incorrect initial diagnosis (eosinophilic colitis) led to unnecessary medical tests and interventions, including a highly restrictive diet. This case highlights the need for higher awareness of the most common causes of rectal bleeding which should be firstly excluded. It also shows a challenging diagnosis in case of several gastrointestinal symptoms that may be associated with more than one possible disorder. Highly restrictive elimination diet in children is related to some risks and should be used only in conditions with some evidence of its efficacy.